Impact-based forecasting for improving the capacity of typhoon-related disaster risk reduction in typhoon committee region - Jixin Yu; Jinping Liu; Ji-Won Baek; Clarence Fong; Michael Fu (Tropical Cyclone Research and Review, 2022)
The two most common types of disasters caused by natural hazards in the Asia-Pacific region are floods and storms, many of them associated with typhoon (tropical cyclone) related impacts. To improve the capacity of typhoon-related disaster risk reduction so as to maximum reduce the losses of people’s life and properties, the decision makers and the public are imminently demanding the information of the targeted impact caused by typhoon. As the front line in hydro-meteorological disaster prevention and mitigation against the typhoon-related disasters, National Meteorological and Hydrological Services (NMHSs) in TC Members have recognized that forecasting impact became more important than forecasting pure causing-disaster elements. Impact-based forecasting signals an evolution from “what the weather will be” to “what the weather will do”. Many things change as impact based forecasts evolve from previous weather forecasts. To enhance impact-based typhoon forecasting, the Typhoon Committee added it into the new updated Strategic Plan 2022–2026. This paper briefed generally the concept of impact based forecasting, introduced the implementation and progresses on typhoon impact based forecasting in TC Members in recent years, and initially discussed the measures and direction for enhancement of impact-based typhoon forecasting and early warning services in future.